GRAMMATICAL ERRORS IN WRITING DESCRIPTIVE TEXT MADE BY TENTH GRADERS OF SMA SWASTA FREE METHODIST MEDAN - Fachri Yunanda; Pesta Anjani Sinaga; Magdalena Pebriola Siahaan; Regina Putri Ginting; Bambang Nur Alamsyah Lubis (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2022)
This research was conducted to identify the various types of errors made in English descriptive texts written by tenth graders at Free Methodist Private High School Medan during the 2022-2023 academic year. This research was conducted on 36 students who became the focus of the research. This research method is descriptive qualitative. Research is conducted offline. Written test-based data collection method. The researcher checked the writing errors of the descriptive texts made by the students. This study concentrates on the categorization of writing errors made by students. The Surface Strategy Taxonomy analysis of the findings revealed 30 inaccuracies in student-submitted descriptive texts. There were 9 addition errors with a total of 30%, 16 errors of omission with a total of 54%, 5 misformation errors with a total of 16%, and 0 ordering errors with a total of 0%. The majority of errors, or 15 out of 30, are spelling (Spelling) errors, which are classed as errors within omission errors. In conclusion, the researchers found 30 errors in the descriptive text written by class X IPS 1 SMA Medan Free Methodis.